Evaluation of canal configuration and frequency of second canal in mandibular lateral incisor using Cone Beam Computed Tomography (CBCT) - Moorpani, Prena; Rehman Qazi, Fazal Ur; Ahmed, Shahbaz; Akhtar, Hira; Shah, Marina; Aziz, Munazza (Pakistan Armed Forces Medical Journal, 2022)
Objective: To categorize root canal configuration according to Vertucci’s classification and determine the frequency of second canal in mandibular lateral incisors of Pakistani subpopulation (Karachi based) by using Cone Beam Computed Tomography.Study Design: Cross sectional study.Place and Duration of Study: Out-patient department of Oral and Maxillofacial Surgery and the department of Radiology at Dow University of Health Sciences, Karachi Pakistan, from Jan to Jul 2019.Methodology: Study was conducted on 160 extracted permanent mandibular lateral incisors. After extraction, teeth were randomly arranged in wax models and imaged via CBCT. Each tooth sample was analyzed in axial and sagittal sections. The images were investigated by two blinded examiners and data on canal morphology was recorded.Results: The frequency of single canal mandibular incisors was recorded as 107 (66.9%) whereas 53 (33.1%) of teeth showed two canals. Females presented with a higher frequency of two canalled incisors, although the results were statistically insignificant. The most prevalent canal anatomy detected was Type I (105, 65.6%) followed by Type III (33, 20.6%), Type II (12, 7.5%) and Type V (10, 6.3%). Mandibular lateral incisors presenting with two canals anatomy, Type III (32, 97%) morphology was most commonly detected followed by Type II (12, 100%) and Type V (9, 90%).Conclusion: CBCT scans are an effective tool for identification of root canal morphology. Mandibular lateral incisors most frequently presented with Type I canal anatomy whereas incisors with two canals most frequently presented with Type III configuration.